Implementasi dan Prinsip Pembelajaran Al-Quran Menggunakan Metode Tilawati Sebagai Pondasi Pemikiran Islam Berbasis Al-Qur’an - Ujang Jenal (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2022)
Learning the Qur’an is the core of Islamic education which emphasizes a deep understanding of the sacred text and the values ​​contained in it. The tilawati method is a significant approach in implementing Al-Quran learning, leading to direct experience in hearing, reciting and understanding Al-Quran verses in depth. This article explores the implementation and principles of learning the Al-Quran using the tilawati method as the foundation of Islamic thought based on the Al-Quran. This approach not only teaches good and correct recitation techniques, but also deepens understanding of the moral values, ethics and life guidelines taught by the Al-Quran. In the context of Islamic education, the tilawati method allows for the holistic integration of Al-Quran values ​​in the educational process, forming a strong Islamic character in the next generation. Thus, the implementation of the tilawati method not only strengthens religious practice, but also makes the Al-Quran the main source of inspiration in developing current and relevant Islamic thought and understanding.